How do real tumors become resistant to cisplatin? - Borst, Piet; Rottenberg, Sven; Jonkers, Jos (Cell cycle (Georgetown, Tex.), 2008)
Lab research on cultured tumor cells selected for resistance to platinum compounds has turned up a diverse array of resistance mechanisms. In contrast, we recently found that mouse mammary tumors containing irrepairable null alleles of the Brca1 gene do not become resistant to cisplatin ever, although they invariably become resistant to a variety of other anti-cancer drugs. Each new treatment with cisplatin shrinks the tumor to a very small remnant, but relapse always occurs. The BRCA1 missing in these mouse tumors is essential for the homology-directed DNA repair (HR) that allows error-free repair of the duplex breaks caused by the excision of platin-DNA adducts. The mouse tumor results therefore raise the question whether the cisplatin resistance mechanisms identified in vitro can actually overcome an irreversible defect in DNA repair in real tumors. This question is underlined by recent analyses of tumor samples of patients with ovarian cancer that have uncovered a new platin resistance mechanism: these tumors were initially sensitive to platin through a defect in the BRCA2 gene, also required for HR, like BRCA1. Resistance in these patients, - after an initial response of the tumor -, was due to secondary mutations in the defective BRCA2 gene, restoring BRCA2 function.1,2 These clinical observations show the overriding importance of a functional HR system for tumor cells to survive platin-induced DNA lesions. Taken together with the mouse mammary tumor data, these observations raise the possibility that proliferating cells have no readily available mechanism to escape from cisplatin DNA damage once their HR is irreversibly inactivated.